2023
DOI: 10.3390/ma16093357
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited and Retarded Behavior by Ca2+ and Ca2+/OD Loading Rate on Ureolytic Bacteria in MICP Process

Abstract: The estimation of optical density (OD) with viable cells is challenging for engineering purposes. In this study, the OD conversion based on previous study was used. The inhibited and retarded behavior of the microbially induced carbonate precipitation (MICP) process was examined. The experimental results showed that high Ca2+ drastically influences the inhibited and retarded behavior on MICP processes. The analysis showed that the inhibition and retardation effects occurred when the Ca2+/OD loading rate exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Murungan et al [44] demonstrated that the completion of urea hydrolysis required a longer time in cementation solutions inoculated with a low amount of bacterial cells due to the insufficiency of bacterial cells, which reduced the level of urease. Nonetheless, Fukue et al [62] stated that a high initial ratio of Ca 2+ /OD and a high concentration of calcium ions may inhibit the processes of ureolytic MICP. A high concentration of calcium ions may cause an electrochemical gradient leading to outflow of protons from the cell [63].…”
Section: Discussionmentioning
confidence: 99%
“…Murungan et al [44] demonstrated that the completion of urea hydrolysis required a longer time in cementation solutions inoculated with a low amount of bacterial cells due to the insufficiency of bacterial cells, which reduced the level of urease. Nonetheless, Fukue et al [62] stated that a high initial ratio of Ca 2+ /OD and a high concentration of calcium ions may inhibit the processes of ureolytic MICP. A high concentration of calcium ions may cause an electrochemical gradient leading to outflow of protons from the cell [63].…”
Section: Discussionmentioning
confidence: 99%